Pliocene Orographic Barrier Uplift in the Southern Central Andes - Pingel, Heiko (2014)
Sedimentary basin fills along the windward flanks of orogenic plateaus are valuable archives of paleoenvironmental change with the potential to resolve the history of surface uplift and orographic barrier formation. The intermontane basins of the southern Central Andes contain thick successions of sedimentary material that are commonly interbedded with datable volcanic ashes. We relate variations in the hydrogen isotopic composition of hydrated volcanic glass (δDg) of Neogene to Quaternary fills in the semiarid intermontane Humahuaca Basin (Eastern Cordillera, northwest Argentina) to spatiotemporal changes in topography and associated orographic effects. δD values from volcanic glass in the basin strata (–117‰ to –98‰) show two main trends that accompany observed tectonosedimentary events in the study area. Between 6.0 and 3.5 Ma, δDg values decrease by ∼17‰; this is associated with surface uplift in the catchment area. After 3.5 Ma, δDg values show abrupt deuterium enrichment, which we associate with (1) the attainment of threshold elevations for blocking moisture transport in the basin-bounding ranges to the east, and (2) the onset of semiarid conditions in the basin. Such orographic barriers throughout the eastern flanks of the Central Andes have impeded moisture transport into the orogen interior; this has likely helped maintain aridity and internal drainage conditions on the adjacent Andean Plateau.